Effects and side effects of European Union assistance on the former Soviet republics. Issue 4 (7th June 2017) - Shyrokykh, Karina
ABSTRACT: Since the early 1990s the European Union (EU) has been the largest donor to the post-Soviet states. In the last decade it more than doubled development assistance to the region. One of the major purposes of assistance is human rights promotion. At the same time, it is still an open question whether, and under what conditions, assistance can improve human rights in recipient countries. This study applies time-series cross-section (TSCS) analysis to identify effects of external assistance. Using data from 12 post-Soviet states over 20 years, I show that conditions under which states are more likely to display a positive effect are high state capacity and political conditionality attached to economic cooperation agreements. Whereas, when state capacity is lower, assistance might cause a slight deterioration of the human rights situation. In hybrid regimes, assistance is associated with negative effects, indicating that external assistance might induce deterioration of human rights in such regimes.